The qualification of a proposed mobile radio system for the karoo core astronomy advantage area - Fynn, Jason Grant (Stellenbosch : Stellenbosch University, 2025)
Fynn, J. G. 2025. The Qualification of a Proposed Mobile Radio System for the Karoo Core Astronomy Advantage Area. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/753d73e8-5748-4b81-9b81-5d456f76ac3e